ANALISIS PENGARUH EASE OF USE, SHOPPING EXPERIENCE DAN ADVERTISEMENT TERHADAP MINAT BELI E-COMMERCE CUSTOMERS TOKOPEDIA DI KOTA BATAM - AZHARI, HENNI; RUSTAM, TRIANA ANANDA (LPPM Universitas Putera Batam, 2021)
On 2020, a lot of e-commerce can be enjoyed on Indonesia. The internet users increasing every years. That can be be one of the most effective opportunities in the business world. Based on the Iprice Insight on Q3 of 2019, Tokopedia has the largest visitors than Shopee. On Q4 of 2020 Shopee matched the number of visitors Tokopedia. This study aims to determine wether there is an analysis the influence of ease of use, shopping experience and advertisement on buying interest e-commerce customers Tokopedia on Batam City. Researches conducted research with a total sample of 385 respondents based on the non probability sampling with sampling purposive. The method of the analysis was carried out using multiple linear regression analysis. Using statistical software SPSS 20. Based on the results of t-test research, it shows that the variable ease of use, shopping experience and advertisement has a positive and significant effect on buying interest, which means that Ha is accepted and Ho is rejected. The results of the f-test research indicate that ease of use, shopping experience and advertisement together have a positive and significant effect on buying interest, which means that Ho is rejected and Ha is accepted. Keywords: Advertisement; Buying Interest; Ease of Use; Shopping Experience